Work Readiness of Graduates Responding to User Needs for a “Ready to Work” Workforce from University Perspective - Sartika, Didi; Nengsi, Ayu Rahma (Institut Agama Islam Negeri Lhokseumawe, 2022)
There is a fundamental difference in the concept of